(untitled) (Huellas, 2024)
The aim of this article is to analyze the integration of qualitative-quantitative and quantitative-qualitative approaches in the methodological strategy. The study constitutes a theoretical nature essay, with a descriptive scope, which identifies the main categories used when referring to integration in the methodological strategy. To achieve this, an integrated analysis is carried out, establishing similarities and differences among each of these categories, to conclude with a proposal that identifies the potential of this type of approach in geographical studies. The complexity of the object of study in social sciences (affected by postmodern logics and linked to globalization) challenges the researcher to seek new flexible alternatives, but at the same time rigorous ones, that allow him to capture the essence of the reality under study. The article highlights the importance of incorporating combined approaches that enables a better understanding of the object of study, from a comprehensive viewpoint. Regarding the research techniques, the study applies a documentary analysis that articulates the systematization and analysis of reference studies in the area, which allowed developing a state of the question reconciling approaches from different fields of social sciences.